Proclamation of new UUM Pro-chancellor at 29th convocation - Daily Express, (KK) (Daily Express (KK), 2016)
ALOR STAR: Former Kedah Menteri Besar Tan Sri Osman Aroff will be proclaimed as the new Pro-chancellor of Universiti Utara Malaysia (UUM) during the university's 29th convocation on Nov 12.